Perlindungan Hak Keperdataan Istri dan Anak dalam Perkawinan Siri : Analisis Siyasah Syari’ah terhadap Celah Hukum Positif & Fiqih - Shabiya Zahra Alifa Koesnaedy; Keisha Rafilah Putri; Muhammad Ilyas Afin Ghani; Rendra Hanam Fadillah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study analyzes the gap in protecting the civil rights of wives in secret marriages (nikah siri) by comparing Indonesian positive law and Islamic jurisprudence (fiqih). Although fiqih munakahat, particularly the Shafi'i School, recognizes the validity of secret marriages when the marriage pillars are fulfilled (parties, guardian, two witnesses, and offer-acceptance), this recognition is not accompanied by state legal protection. Law Number 1 of 1974 on Marriage adds a registration requirement as a condition for administrative recognition, creating a legal dualism: valid under fiqih but unrecognized by positive law. As a result, wives in secret marriages lose protection over their rights to maintenance (nafkah), inheritance, joint property (gono-gini), and dignity before the court. Additionally, contemporary Islamic scholars, through the maqasid al-shariah approach and the dar'ul mafasid principle, consider secret marriages prohibited because they cause significant harm (mafsadat) to women, creating a disjuncture between conservative and contemporary fiqih. This regulatory gap demonstrates the absence of effective legal enforcement mechanisms to uphold the rights of wives in secret marriages, even though fiqih has established these rights normatively.